Flaps for lower limb diabetic wound reconstruction: A systematic review and meta-analysis. (April 2023) - Tan, Choon Han; Wu, Yanlong; Satkunanantham, Mala
Summary: Background: The treatment of chronic diabetic wounds includes wound dressing, debridement, flap surgery, and amputation. For suitable patients with nonhealing wounds, locoregional flaps or free flaps may be used. This paper aims to review the outcomes of flap surgery and identify the risk factors for flap loss. Methods: MEDLINE, Embase, and Cochrane Library were searched. Articles reporting flap loss outcomes for flap surgery in lower limb chronic diabetic wounds were included. Case reports and case series with fewer than five patients were excluded. A subset of articles was used for revascularization subgroup analysis and another subset for meta-analysis of risk factors for flap loss. Results: In the free flap group, the total flap failure rate was 7.14% and partial flap failure rate was 7.54%. The rate of major complications requiring operative takeback was 19.0%. Early mortality was 2.76%. In the locoregional flap group, the total flap failure rate was 3.24% and partial flap failure rate was 5.36%. The rate of major complications requiring operative takeback was 13.3%. There was no early mortality. The rate of free flap loss was 18.2% with revascularization, significantly higher than 6.66% without revascularization. Conclusions: Our findings concur with previously published studies on flap loss and complications in diabetic lower limb wounds. There is an increased risk of flap loss in patients who require free flap and revascularization compared to patients who only require free flap. This could be because of the fragile and fibrotic vessels found in diabetics with comorbid atherosclerosis.